PENGARUH MEDIA PEMBELAJARAN CARD SORT TERHADAP HASIL BELAJAR PENDIDIKAN PANCASILA SISWA KELAS IV SEKOLAH DASAR NEGERI 1 KERU - Lale, Lale Tita Hardya Iswari; Nisa, Khairun; Sobri, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of using the card sort media on the learning outcomes of Pancasila Education for fourth-grade students at State Elementary School 1 Keru. This research is a quantitative study with a quasi-experimental design using a pretest-posttest group design. Data collection techniques used are observation and tests. In this study, hypothesis testing was conducted using a simple t-test. The hypothesis test results showed that tcount 2.288 > ttable 2.018 with a significance value (2-tailed) of 0.027, which means 0.027 < 0.05. Therefore, H0 is rejected, and Ha is accepted. This indicates that the card sort media has a positive impact, and students achieve improved learning outcomes in Pancasila Education for fourth-grade students at State Elementary School 1 Keru.